Logiques et contradictions du trafic transalpin dans le contexte politique et social européen - Manfred Perlik (Revue de Géographie Alpine)
In the Alpine regions, two conflicting interests exist: One part complains about a lack of accessibility. The other part is connected to international roads and is mainly affected by the impacts of transalpine traffic. These regions frequently argue that a great deal of such transports are superfluous or needless. This article is based on a study which discusses the following questions: 1 - Is there any needless transport that could be removed without substitution? 2 - Are strategies of changing modal split or market solutions as road pricing sufficient to reduce transport and its impact? 3 - Under what conditions may transport be reduced in a more comprehensive manner? Answers are given by analysing three fields relevant for traffic growth in their internal coherence: the political logic, the economic logic, and the logic of spatial development. They are interpreted within a regulationist approach. But there are contradictions within different primary societal/political goals as well as between these goals and economic ones, especially the contradiction between competitiveness and equal living conditions in different regions. Such contradictions can be explained by the process of European unification, by the different interests of the most important stakeholders, and by the change of values in the last 30 years that may be characterised as a regime change. The three logics are man-made rapports and therefore subject to change by the stakeholders in the long run. According to the concept of sustainable development on a global level and in the interest of the regions concerned, more radical solutions within the meaning of a revisited regime of accumulation and regulation respectively, should be considered, which may be valid in the long run.